British Catholics and the Mass Media - Grant, Kevin R. (Communicatio socialis, 1978)
Introduction: The Cockle and The Wheat. It is beyond the power of parents or of pastors today to monitor the tide of the mass media in Britain as it passes over those they might protect. Exposure to all sorts of ideas and images is now an inescapable part of the general risk of life; and the carefulness of Christians in what they contribute to or select from the output of the media can counteract but cannot significantly dilute the contrary messages.It is a fallacy that any one medium is or ever will be the best or most important in any absolute sense. The media merge; and competence in their employment requires a knowledge of the character and reach of each type so that messages may be conveyed to chosen groups. Christian practitioners in the media need to master this orchestration. It may be regretted in this connection that we have in this country no single professional guild of Catholic or Christian media workers. (...)